Hydroxyapatite composites with multiwalled carbon nanotubes - Ewa Skwarek; Yuliia Bolbukh; Władysław Janusz; Valentyn Tertykh (Adsorption Science & Technology)
The structure of composites based on hydroxyapatite filled with multiwalled carbon nanotubes was investigated using differential scanning calorimetry analysis and X-ray diffraction spectroscopy. Hydroxyapatite was prepared by the wet synthesis in the presence of pristine and oxidised carbon nanotubes. An influence of nature of functional groups of the nanotubes boundary layer on a crystallinity of the inorganic part was evaluated using differential scanning calorimetry analysis and X-ray diffraction spectroscopy. Morphology of composites obtained was studied by nitrogen adsorption/desorption technique and scanning electron microscopy. The hydroxyapatite/nanotubes interface was characterised using electrochemical methods. The parameters of the electrical double layer: A density of surface charge versus pH, zeta potential versus pH were described. The study has shown that the synthesis of hydroxyapatite/nanotube composites by formation of inorganic part in the presence of carbon filler significantly affect the microstructure, phase composition, crystallinity, hydroxyl content, chemical composition of the mineral part, as well as thermal properties and electrokinetic properties of composite.